Cutaneous endometriosis - Liza Raffi, BS; Raagini Suresh, BS; Timothy H. McCalmont, MD; Amanda R. Twigg, MD (Wolters Kluwer, 2019)
Cutaneous endometriosis is a disorder that primarily affects women of reproductive age. The disorder is most commonly associated with cyclical pain during menses, but it can be difficult to diagnose in the absence of these symptoms and requires biopsy testing for a definitive diagnosis. We report on a case of a 41-year-old patient undergoing hormonal therapy for infertility who presented with a painful firm subcutaneous nodule in the umbilicus. She was ultimately diagnosed with cutaneous endometriosis and underwent surgical excision. In this report, we discuss the differential diagnosis and comment on treatment options, including surgical excision with wide margins or treatment with hormonal agents, such as danazol or leuprolide. Finally, we discuss whether patients with cutaneous endometriosis should receive an additional evaluation for pelvic endometriosis. Keywords: Cutaneous endometriosis, endometriosis, hormone therapy